(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
The article presents data from modern scientific literature devoted to the study of adverse toxic effects of certain new-generation pesticides on the human body. It highlights the potential carcinogenic, mutagenic, gonadotropic, and cumulative properties of pesticides, as well as their possible effects on the structures of the brain’s biological barriers, blood, enzymatic, immune, and endocrine systems when exceeding permissible doses. It is emphasized that further research on the clinico-morphological and toxicological characteristics of pesticide intoxications will contribute to improving preventive measures and providing a scientific basis for the forensic medical assessment of poisoning cases caused by these chemical substances.